Pengembangan Assessment for Learning (AfL) melalui Lesson Study pada Praktik Pemesinan SMK Sesuai Kurikulum 2013 - Endri Triwiyono (Jurnal Dinamika Vokasional Teknik Mesin, 2017)
The aim of this research is to: (1) develop an assessment for learning (AFL), and (2) verify the effectiveness of the AFL through lesson study approach on machining practice in SMK. The research was a research and development with Borg & Gall's modified R&D model which comprised of 3 phase: development, small scale test, and large scale test. The research subjects were the students and teachers of machining program at SMK 2 Depok Sleman. Data were collected through interviews, documentation, questionnaire, notes, observation sheet, assessment sheet, and students' response. The descriptive analysis technique was used to analyze the data using rating methods. Results of the research show: (1) an assessment for learning through lesson study approach was successfully developed which consists of the assessment process and the product. Results of the assessment informs about students' processes in practice learning, product quality and overall practice results to determine students' achievement and also serves as formative feedback; (2) the effectiveness of the assessment, which was reviewed for eligibility, was categorized as "very good", whereas from the reliability it was in "good" category. The effectiveness was rated "very good" for its reliability. The implementation was in "good" category with 76.58% implementation and students' response were good. Penelitian ini bertujuan untuk: (1) pengembangan perangkat assessment for learning, (2) menguji keefektifan perangkat assessmen for learning melalui pendekatan lesson study pada pembelajaran praktik pemesinan. Penelitian pengembangan ini menggunakan modifikasi model Borg & Gall yang terbagi menjadi 3 tahap yaitu: pengembangan, tahap ujicoba terbatas, dan tahap ujicoba diperluas. Subjek penelitian adalah siswa dan guru teknik pemesinan SMK Negeri 2 Depok Sleman. Pengumpulan data menggunakan wawancara, dokumentasi, angket kuesioner, catatan lapangan, lembar pengamatan, lembar penilaian produk serta respon siswa. Teknik analisis data menggunakan analisis deskriptif dengan metode rating. Hasil penelitian menunjukkan bahwa: (1) perangkat penilaian assessment for learning melalui pendekatan lesson study berhasil dikembangkan berupa perangkat penilaian proses dan produk. Informasi hasil penilaian yaitu informasi akurat proses kerja siswa, kualitas produk serta hasil keseluruhan penilaian praktik untuk mengetahui capaian belajar siswa dan sebagai formatif feedback; (2) efektifitas perangkat ditinjau dari keberfungsian mempunyai hasil penilaian "sangat baik" dan untuk reliabilitas "baik". Keefektifan perangkat masuk kategori "sangat baik" ditinjau dari hasil penilaian dan reliabilitasnya. Tingkat keterlaksanakan masuk kategori "baik" dengan persentase keterlaksanaan 76,58% dengan respon baik dari siswa.